Assessment of Antimicrobial Use for Companion Animals in South Korea: Developing Defined Daily Doses and Investigating Veterinarians’ Perception of AMR - Sun-Min Kim; Heyong-Seok Kim; Jong-Won Kim; Kyung-Duk Min (Animals)
There are global concerns regarding the transmission of antimicrobial-resistant pathogens from animals to humans. Especially, companion animals are increasingly recognized as a potential source due to their close interactions with people, despite a limited number of reported cases. Although, social demands regarding comprehensive surveillance for antimicrobial resistance (AMR) among companion animals are highlighted, there is a lack of a relevant system in South Korea. In this regard, we conducted preliminary investigation on antimicrobial use (AMU) among small animal clinics, along with veterinary practitioner’s knowledge and attitude regarding this issue in South Korea. We collected data on 684,153 antimicrobial prescription visits for canine and feline patients from 2019 to 2022 at 100 veterinary facilities in South Korea, using electronic medical records. To evaluate antimicrobial use (AMU) and facilitate comparisons across institutions and time periods, we developed the Defined Daily Dose for Animals (DDDA) and the Defined Animal Daily Dosages per 1000 Animal-Days (DAPD). In addition, we conducted an online survey of 362 veterinary practitioners, which included questions on their perceptions, attitudes, and practices regarding antimicrobial prescriptions. Simple frequency analyses were performed to examine temporal trends, regional differences and variations by facility size in AMU, and to summarize survey responses. Descriptive analysis using data from 100 veterinary clinics revealed a rising trend in AMU between 2019 and 2022, with higher usage observed in larger clinics and non-capital regions. DDDA values for dogs were generally higher than for cats. Survey results highlighted that, while veterinarians exhibited high awareness of AMR, prescribing practices were significantly influenced by clinical judgments and owner demands, often deviating from established guidelines. The adoption of an electronic veterinary prescription management system (e-Vet) was proposed to enhance antimicrobial stewardship. However, concerns regarding the system’s efficiency and administrative burden were prominent. To our best knowledge, this study provided DDDA for companion animals for the first time in South Korea. Although the indicator should be improved with more comprehensive data and expert opinion, our study showed that it enables reasonable situation analysis regarding AMU in companion animals. The identified factors that affect veterinarians’ prescription practices can also be used to design an effective strategy for promoting appropriate antimicrobial usage.